Malay language learning innovation in enhancing essay writing performance - Jamian, Abdul Rasid; Mohamad Ali, Yusliza; Md Sabil, Azhar; Othman, Shamsudin (Human Resource Management Academic Research Society, 2018)
This study aimed to get information about essay writing using the Frog Virtual Learning Environment (VLE Frog). A total of 60 samples of Form Four students in Kuala Lumpur Technical School were selected and divided into experimental group and control group. Quasi-experimental study was conducted to see the performance in essay writing, grasping the main idea and amplifying the contents. Results of t-test analysis in the post-test indicated that the ratio of the total marks for the experimental group and the control group showed significant differences in the t (58) = 3.219, p <0.05. Meanwhile, finding analysis in grasping the main idea in post-test did not show a significant different which is t (58) = 1.287, p<0.05. Results of t-test analysis essay content amplification between the two groups have shown that there was a significant difference in treatment between the two groups of contents at t (58) = 4.264, p <0.05 In conclusion, the use of VLE Frog in teaching essay writing has proven to be more effective than teaching by using traditional teaching methods even though grasping the essay content has less impact on the students’ achievement. Hence, the findings of this study may encourage the teachers to adapt teaching VLE Frog in essay writing and student will be more interested in writing essays.